Traditional Poultry Supply and Marketing in the City of N’Djamena in Chad - Youssouf, Issa; Youssouf, Mopate Logtene; Soumarkamla, Djougui; Ayao, Missohou (International Journal of Poultry Science, 2012)
The study characterized the supply and the marketing of traditional fowls in the markets of the city of N’Djamena. It surveyed 104 tradesmen including 29 wholesalers retailers, 61 retailers and 14 peddlers chosen at random in six markets distributed in 5 districts of N’Djamena. The crosscutting and retrospective investigation is carried out among salesmen. Observations were made on chickens slaughtered for sale at the market. The tradesmen aged 35.4±10.8 years are mostly (96%) Moslem and illiterate tradesmen (63%) who started (75%) their trade between the 1990s and 2000s. Wholesalers and retailers get their supplies especially (63%) in the Hadjer Lamis (39%), Western Tandjilé (18%) and Eastern Mayo-Kebbi (6%) regions. As for the peddlers (13%), they get their supplies from the markets in N’Djamena where the fowls are sold. Transportation is done using trucks (58%) and cabs (28%) by the other tradesmen and on foot (14%) downtown by the peddlers. Packing is especially made up of single cages (73%). Out of 542 fowls lost during transport, chickens constitute 91% of the losses, pigeons 8% and guinea fowls 1%. These losses are estimated at 1004150 F CFA. Major customers are housewives (34%) while 66% of others are found especially among restaurant owners and street meat grill operators. Out of 3701 fowls sold per day, 92% are chickens of an average live weight of 1047 G and a carcass weight of 681 G. About 2713 birds representing 73% of the fowls are slaughtered and plucked right at the market places. The average sale prices are 2660 F CFA for a chicken, 2270 F CFA for a guinea fowl, 2990 F CFA for a duck and 715 F CFA for a pigeon. The average gross gain made from the not well sold ducks is higher (p<0.001) than that from the other species. The organization of the actors and an improvement of the constraints will allow a better supply of the markets with traditional poultry.